Role of desalination in addressing water scarcity - United Nations. Economic and Social Commission for Western Asia. (New York United Nations, 2009)
"Chapters I and II examine the water supply and demand situation in the ESCWA region and provide a background on desalination capacities. Chapter III reviews the most common desalination technologies employed in the region. Chapter IV analyses the full cost of providing desalinated water from the plant to the consumer's tap. Chapter V reviews ways of reducing the cost of desalination and discusses the potential of using renewable and nuclear energy sources for desalination. Chapter VI concludes the report and provides some recommendations for decision makers and the desalination industry."--Introd
"Sales No. E.09.II.L.7"--T.p. verso.
Full text also available online.
Keywords: Saline water conversion -- Costs. -- Middle East; Water resources development -- Middle East; Water-supply -- Middle East